Endoscopic dacryocystorhinostomy with silicon stent: our experience - Suri, Neeraj; B. M., Bhavya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Dacryocystorhinostomy is the current surgical modality of treatment preferred for patients with nasolacrimal duct obstruction. Both external and endonasal endoscopic approaches have been in practice with their own merits and demerits. Since the invention of endoscopes, endoscopic DCR is preferred for its scarless, minimally invasive technique and many modifications have been done over years like placement of silicon stents to reduce recurrence. Methods: In our study we evaluated 70 patients with epiphora with obstruction in nasolacrimal duct, Fresh cases and revision cases who had undergone either external and/ endoscopic DCR without stent were included. All patients underwent endoscopic dacryocystorhinostomy (DCR) with silicon stent placement. Patients were followed postoperatively for a period of 6 months to 3 years. Results: The results were compared with that of external DCR and endoscopic DCR without stent. In our study we found that, endoscopic DCR with silicon stent had less chances of recurrence and synechiae formation. Results at 3 years follow up have been good with 95.7% patients relieved of symptoms completely. Conclusions: Endoscopic DCR is a cost effective and a safe alternative for External DCR in patients with nasolacrimal duct obstruction. We found that endoscopic DCR with stenting had several advantages over more conventional external approach.